2014
DOI: 10.1111/1556-4029.12546
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Deaths: A Retrospective Review of New Mexico's Cases, 1977–2009

Abstract: To better understand lightning deaths, a retrospective review of electronic records from New Mexico's Office of the Medical Investigator database was performed between 1977 and 2009 to update and assess current risk factors. Information on demographics, circumstances, autopsy, and death certificates were collected and analyzed. Fifty-four decedents were identified, ages 2-71 years old (mean 34 years old), 42 males and 12 females. Common racial/ethnic groups were non-Hispanic Whites and American Indians (togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…By contrast, a decline in lightning fatalities in recent decades has been reported from developed countries 24 – 27 , reasons for which are: development of medical responses and treatments; education of the public; meteorological warnings; and improved building codes for lightning protection. The latter include housing structures with grounded plumbing, electric conducting materials, improved fire resistance of homes, and lightning rods 28 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a decline in lightning fatalities in recent decades has been reported from developed countries 24 – 27 , reasons for which are: development of medical responses and treatments; education of the public; meteorological warnings; and improved building codes for lightning protection. The latter include housing structures with grounded plumbing, electric conducting materials, improved fire resistance of homes, and lightning rods 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings of aspiration pneumonia, pulmonary oedema and alveolar haemorrhages may also be there. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…[15] In another study involving 54 cases in New Mexico, the mean age was reported to be 34. [18] In the study of Hekimoglu and et al, the average age of cases died due to lightning strike was 23.5. [16] The mean age of the cases in the present study was 39.66±13.36 (min: 18, max: 56).…”
Section: Agementioning
confidence: 96%
“…), and a larger part (72.2%) in non-working activities (sport outdoors, fishing, camping, boating, etc.). [18] In the study of 47 cases died by lightning strike, 48.9% of the cases were reported to be farmers. [14] In the study of Hekimoglu et al, was reported that 36.4% of cases were soldier and 36.4% were farmer.…”
Section: Scenementioning
confidence: 99%